2017
DOI: 10.4013/nbc.2017.123.06
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of nonvolant mammals in a Caatinga area in northeastern Brazil

Abstract: The Caatinga is an exclusively Brazilian biome that covers approximately 11% of the country and is currently vulnerable to a series of impacts. Its biodiversity is relatively poorly-known, and few data are available on most groups of fauna, hampering the reliable identification of priority areas for conservation. The present study describes the species composition and diversity of the nonvolant mammal community from the Serra das Almas Nature Reserve, an advanced outpost of the Caatinga Biosphere Reserve. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
4
1
2
Order By: Relevance
“…Herpailurus yagouaroundi was the most commonly observed species in photographic records (n = 36; 16.4 % of the total). Our results contrast sharply to the literature on the species, which suggests that this small felid occurs in low densities and yields few records (Almeida et al 2013, Dias et al 2017, Marinho et al 2018.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Herpailurus yagouaroundi was the most commonly observed species in photographic records (n = 36; 16.4 % of the total). Our results contrast sharply to the literature on the species, which suggests that this small felid occurs in low densities and yields few records (Almeida et al 2013, Dias et al 2017, Marinho et al 2018.…”
contrasting
confidence: 99%
“…These two protected areas have the same vegetation type as the study area. Recent mammal inventories carried out in the Caatinga in neighboring states indicated the occurrence between seven and 24 medium and large species (Deiciellos, 2016, Dias et al 2017, Marinho et al 2018.…”
mentioning
confidence: 99%
“…Interactions with these species should be modeled whenever possible in order to obtain better knowledge of small felid habitat preferences in privately-owned areas. A study carried out in the Private Natural Heritage Reserve Serra das Almas, in the Brazilian state of Ceara ´, a reserve with twice the area of Fazenda Ranch, indicated that tiger cats and jaguarundis are very rare, most likely due to the locally-abundant ocelot [84]. Interestingly, in Boqueirão da Onc ¸a National Park, in the Caatinga of Bahia, ocelots, which were highly abundant, had a high temporal overlap with tiger cats, but had no effect on habitat use by jaguarundis.…”
Section: Plos Onementioning
confidence: 99%
“…O número de inventários de mamíferos realizados neste bioma tem aumentado nos últimos anos (e.g., Feijó & Langguth 2013, Delciellos 2016, Marinho et al 2018a, Aximoff et al 2021. No entanto, há um déficit histórico de estudos e investimentos em pesquisa na Caatinga, fazendo com que grande parte de sua área e biota permaneça desconhecida ou subamostrada (Santos et al 2011, Dias et al 2017Marinho et al 2018a, Aximoff et al 2021. Um exemplo disso é que, até o momento, apenas um estudo sobre mamíferos de médio e grande porte foi realizado na Caatinga do estado do Piauí, tendo registrado 13 espécies, sendo cinco por registros das armadilhas fotográficas (Delciellos 2016).…”
unclassified